Russell Kirk: A Critical Biography of a Conservative Mind - Person, James E., (Madison Books, 1999)
This first full-length treatment of Russell Kirk's life and accomplishments blends new biographical insights and critical perspectives about the author of the ground-breakingThe Conservative Mind.